The Integration of Local Cultures in English Teaching Materials in Promoting Culturally Responsive Teaching - Lathifa Azhary; Sitti Fatimah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Integrating local cultures in English teaching materials is crucial for promoting cultural diversity, cultural sensitivity, and enhancing their language learning experience. By incorporating local elements, teachers can make the learning content more relatable and engaging for students, ultimately leading to a more inclusive and effective educational environment. The purpose of this study was to find out the integration of local cultures in English teaching materials designed by the pre-service English teachers. The research participants were ten pre-service English teachers (PPG students 2022) from West Sumatera, Jambi, West Kalimantan, South Kalimantan, and South Sulawesi. The teaching materials as a source of the data were collected from their teaching experiences during PPG programs. Furthermore, the researcher found the participants through various social media platforms (Instagram, Telegram, and WhatsApp). Through social media, the researcher got the materials. The data was analyzed by using a document checklist based on Moran’s theory. The research showed that local cultures were incorporated in teaching materials designed by pre-service English teachers in three dimensions: product, practices and perspectives dimension.